The Existence of Islamic Boarding Schools in Improving Public Education - Mochamad Mawahib; Ahmad Sunoko (Tarbiyah Departement collaboration with AMCA, 2022)
The role of Islamic boarding schools in improving public education and how the existence of Islamic boarding schools changes the way people think and attitudes about the importance of education. This study aims to determine the presence of Pondok Pesantren Al Anwar 2 in improving the level of public education and the pattern of its implementation. This study uses a qualitative approach. Data collection is done by interview, observation, and documentation. Data analysis, data reduction, data presentation, concluding and checking the validity of the findings with the degree of trustworthiness, transferability, dependability and confirmability. The study results are as follows: Pondok Pesantren Al Anwar 2 in improving the level of community education is by developing the existing curriculum, instilling an attitude of tawadu', and establishing good relations with the community. The pattern of implementing Islamic boarding schools' existence in improving community education is equipping students with theoretical and practical knowledge and inviting the community to learn and implement religious guidance. Some of the activities initiated by Al Anwar 2 Islamic Boarding School to improve community education are programming various activities, including khataman Akhiru Sanah, hadrah art training, recitation, clean Friday and bathsu al masail during yasinan and other activities.